SCL-90-R and Suicide Ideation in Torture and War Survivors Receiving Psychotherapy - Ladislav, Valach, (Journal of Cognitive Behavioral Therapy, 2018)
Objectives: Torture survivors suffer psychosocial distress such as posttraumatic stress disorder (PTSD) and depression. Patients with PTSD and depression have increased risk for suicidal behavior. The aim of this study is to identify those torture and war survivors who have suicidal thoughts and describe their psychological profile as assessed in SCL-90-R. The patients of the Swiss Red Cross Centre for Torture Victims receiving psychotherapy were monitored with the SCL-90-R (N=58). Results: Out of 56 patients 32 (57%) declared that they did not suffer under the thought to end their own life (0=not at all), 10 (18%) indicated that they suffered substantially (scale value 3) or extremely (4) while 14 (25%) suffered somehow (1, 2). The endorsement of the suicide ideation correlates highly with all SCL-90-R scales, particularly with the scale Depression and PTSD indicating that the patients with suicide ideation also show considerable psychopathology. The scale Depression explained 40% of the variance of the suicide thoughts item and the scale Anger-hostility added another 5%. Conclusion: Suicide prevention should be an important part of the treatment and care in dealing with war and torture survivors.
Keywords: torture survivors; suicide ideation; SCL-90-R; PTSD; depression